Corrosion Protection of Stainless Steel by Electro Polymerization of 4- (2-Hydroxy Benzamido) -4- Oxobut- 2 -Enoicacid and Study its Biological Activity - Sana A. Habeeb (Journal of Global Pharma Technology, 2016)
Poly4-(2-hydroxy benzamido)-4-oxo but-2-enoi cacid (PHOE) was prepared by the electrochemical polymerization of 4-(2-hydroxy benzamido)-4-oxobut-2-enoicacid (HOE) monomer on stainless steel (St.S)   asanti -corrosion coating.  Atomic Force Microscope (AFM), Fourier transform infrared techniques (FTIR) and cyclic voltammetry were used to characterize the properties and the structure of the polymer layer.  The corrosion behavior of  uncoated and coated  St.S were estimated from Tafels plots using Potentiostatic  technique in 0.2 M HCl solution as  corrosive environment  at temperature range( 293 – 323) K. Nanomaterials such as  graphene and Nano ZnO in the different concentrations were added to monomer solution to improve the corrosion resistance  of  St.S surface so that  the results showed  that the values of  corrosion  protection efficiency  for  polymeric  coating increase with adding Nanomaterials . In addition the kinetics and thermodynamics parameter were calculated for St.S corrosion   before and after polymeric coating in the acidic medium, moreover, the influence of the prepared polymer on some strains of bacteria was studied.Keyword: Anti-corrosion, Electrochemical polymerization, Stainless steel, Coating, Antibacterial activity.